2019
DOI: 10.1002/ejlt.201900143
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Analyzing Fatty Acids in Cattle Hair, with Special Emphasis on Lauric Acid and Myristic Acid

Abstract: This study is aimed at improving a protocol for measuring fatty acids in cattle hair with respect to sensitivity, repeatability, and speed to increase its applicability as a biomarker. For the investigation, 14 hair samples from German Holstein cows are used. Alternative methods for grinding the hair (mortar vs mill), lipid extraction (modified Folch vs kit extraction), and solvent evaporation before injection on a gas chromatograph (evaporated vs unevaporated extracts) are tested. Hair ground with a mill comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Lipid extraction and fatty acid derivatization were carried out using a lipid extraction kit (Möller et al 2019) in conditions reported earlier (Özek et al 2018). The lipids were typically extracted using a dual solvent partition system containing a lipophilic solvent and an aqueous solvent.…”
Section: Lipid Extraction and Fatty Acid Derivatizationmentioning
confidence: 99%
“…Lipid extraction and fatty acid derivatization were carried out using a lipid extraction kit (Möller et al 2019) in conditions reported earlier (Özek et al 2018). The lipids were typically extracted using a dual solvent partition system containing a lipophilic solvent and an aqueous solvent.…”
Section: Lipid Extraction and Fatty Acid Derivatizationmentioning
confidence: 99%
“…Hair lipids were extracted from 200 mg of cleaned and mill-ground hair. The protocol was recently described in detail and is provided in Möller et al [17]. A reference standard mixture was used to identify the different fatty acids via high-resolution gas chromatography (see supplements for a total list of fatty acids).…”
Section: Analysis Of the Fatty Acid Composition Of Bovine Hairmentioning
confidence: 99%